Prognostic Stratification Based on a Novel Nomogram for Solitary Large Hepatocellular Carcinoma After Curative Resection - Zhuang, Hongkai; Zhou, Zixuan; Ma, Zuyi; Huang, Shanzhou; Gong, Yuanfeng; Zhang, Zedan; Hou, Baohua; Yu, Weixuan; Zhang, Chuanzhao (Frontiers in Oncology, 2020)
Solitary large hepatocellular carcinoma (SLHCC) is a specific subtype of HCC with unique characteristics. It is of great interest to assess and stratify the prognosis of SLHCCs after curative resection. In this study, we tried to construct a prognostic nomogram for SLHCC following curative resection through a retrospective analysis of 202 SLHCC cases. Seven prognostic factors were identified and integrated to establish a novel prognostic nomogram, which included tumor size, microvascular invasion, tumor differentiation, Ki67 (%), α-fetoprotein (AFP), carbohydrate antigen 125 (CA125), and HBsAg status. The Harrell's concordance index (C-index) of the nomogram for overall survival (OS) in the training, validation, and whole sets was 0.752, 0.703, and 0.733, respectively. Furthermore, the area under the curve (AUC) of the receiver operating characteristic (ROC) curve of the nomogram for predicting 1-, 3-, and 5-year OS indicated that the nomogram had an optimal discrimination of the prognostic prediction for SLHCC. The total score of each patient was calculated based on the nomogram, and patients were divided into three subgroups: low-risk group (total score ≦ 107), medium-risk group (107 < total score ≤ 125), and high-risk group (total score > 125). The 1-, 3-, and 5-year OS rates of the low-risk, medium-risk, and high-risk groups in the whole set were 89.3 vs. 70.1 vs. 33.3%, 76.6 vs. 37.8 vs. 14.5%, and 69.8 vs. 25.1 vs. 12.5%, respectively (P < 0.001). Similar results were shown in terms of the recurrence-free survival (RFS) rate. By analyzing 101 cases of recurrent tumors, transarterial chemoembolization (TACE) plus radiofrequency ablation (RFA)/surgery was found to prolong patient survival when compared to TACE alone in the low-risk group, but not in the medium/high-risk group. In conclusion, our prognostic nomogram successfully stratifies the prognosis for SLHCC after curative resection, which deserves further study in future clinical practice.